BUCKLING BEHAVIOUR OF ANGLE SECTION BEAM WITH THE UNSTIFFENED FLANGES IN COMPRESSION - Sivakumar, Dhar Malingam; Sivarao, Subramonian; Ahmad, Rivai; Tan , Chee Fai; Mohd Radzai , Said (2006)
Under certain condition, usually involving compressive stresses a structural member may develop large distortions under critical loading conditions. This condition can be described as buckling. Twenty cold formed galvanized mild steel angle sections were tested in four-point bending with the unstiffened flanges in compression. Thickness of 1.00 mm and 1.50 mm with angles from 0° to 22.5° were used. As the thickness and angle increases the maximum load increases while the deflection reduces.